2019
DOI: 10.1002/ags3.12285
|View full text |Cite
|
Sign up to set email alerts
|

Background characteristics and postoperative outcomes of insufficient weight loss after laparoscopic sleeve gastrectomy in Japanese patients

Abstract: AimLaparoscopic sleeve gastrectomy (LSG) is becoming popular in Japan, but insufficient weight loss is often observed in patients after LSG. We investigated the effect of LSG on obesity‐related comorbidities and identified the background characteristics of Japanese patients with insufficient weight loss after LSG.MethodsIn this multi‐institutional retrospective study at 10 certified bariatric institutions, 322 Japanese patients who underwent LSG with a follow‐up period of more than 2 years were analyzed. Anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…The U-shaped relationship between frequency of mental disorders and %TWL was reported for the first time by J-SMART [6], and their finding is supported by the present study. A previous study reported that mood disorders were the most common mental disorder in obese individuals, followed by binge eating disorder and anxiety disorders [15].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The U-shaped relationship between frequency of mental disorders and %TWL was reported for the first time by J-SMART [6], and their finding is supported by the present study. A previous study reported that mood disorders were the most common mental disorder in obese individuals, followed by binge eating disorder and anxiety disorders [15].…”
Section: Discussionsupporting
confidence: 90%
“…A previous review concluded that one study found no difference in weight loss at 1 year but less weight loss at 4 years in patients with preoperative depression, but 4 other studies found no difference in postoperative weight loss between patients with and those without preoperative depression [14]. The U-shaped relationship between frequency of mental disorders and %TWL was reported for the first time by J-SMART [6], and their finding is supported by the present study. A previous study reported that mood disorders were the most common mental disorder in obese individuals, followed by binge eating disorder and anxiety disorders [15].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations